If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + 2x = -12 + 13x Solving -8 + 2x = -12 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -8 + 2x + -13x = -12 + 13x + -13x Combine like terms: 2x + -13x = -11x -8 + -11x = -12 + 13x + -13x Combine like terms: 13x + -13x = 0 -8 + -11x = -12 + 0 -8 + -11x = -12 Add '8' to each side of the equation. -8 + 8 + -11x = -12 + 8 Combine like terms: -8 + 8 = 0 0 + -11x = -12 + 8 -11x = -12 + 8 Combine like terms: -12 + 8 = -4 -11x = -4 Divide each side by '-11'. x = 0.3636363636 Simplifying x = 0.3636363636
| 73=x+17 | | 2x+13=42-9x | | 27-4x=7-9x | | 16x^2+35x=125 | | y^2+8y+48=0 | | -2+4x=-8+19x | | 4x+11=-37-4x | | 107=4x+11 | | 16x^2+35x+167=0 | | 11x-5=x+2 | | (4a^2b)(-3a^3b^2)= | | 17=-5t^2+20t+2 | | 5+3b=8 | | 50=18x-22 | | 1+6x=11+x | | 31-5x=7-9x | | 6x+14=-56-4x | | 7+4x=1+x | | 5=-2x+27 | | 0=-5t^2+20t+2 | | 3+7(-8x-6)=-1+2(2-7x) | | 10a+32= | | 8x-3=3x-22 | | 2=-2x+20 | | 11x-9=5x+2 | | 2c+5d=11 | | -7(8+8k)-2(4+5k)=-64 | | 36=5x+6 | | y=3x^2-28x+49 | | 2(5+3)=4(x-1) | | -1+x+2=4x+1 | | 2(x-1)+2x-1=4x-3 |